Wireless body area network: Architecture and security mechanism for healthcare using internet of things - Arun Kumar; Ritu Dewan; Wisam Subhi Al-Dayyeni; Bharat Bhushan; Jayant Giri; Sardar MN Islam; Ahmed Elaraby (International Journal of Engineering Business Management)
Internet of Things (IoT) enabled wireless body area network (WBAN) is a novel technology that combines medical, wireless, and non-medical devices for healthcare management applications. Indoor healthcare institutions, such as hospitals, may employ IoT devices to manage medical equipment, maintain inventory, and monitor patients. In addition to monitoring temperature, humidity, and air quality, IoT sensors may help prevent the spread of sickness. The data generated by small sensor devices need strong security methods for secure transmission over a public network. Security of the data sent from source to destination is handled by transport layer security (TLS) protocol and prevent message loss or reordering. The most difficult component of TLS is determining how to handle reliability. Low-power wireless networks employ the Datagram Transport Layer Security (DTLS) protocol to solve this problem. But if the Server is exposed to a malicious attack (i.e., flooded with ClientHello messages, the DTLS protocol may no longer serve the purpose) as it may lead to Denial-of-Service (DoS). The paper proposes an intelligent gateway-based verification and approval system to protect health data from IoT wearable devices, a key worldwide data security risk. Paper used Contiki Network Simulator for designing an advanced smart gateway-based constrained application Improved DTLS (CoAP I-DTLS) security protocol. To assess the effectiveness of the proposed work, the packet loss ratio is computed for the CoAP, CoAP-DTLS, and CoAP I-DTLS protocols. To assess the effectiveness of the improved CoAP I-DTLS, calculations are also made for data transfer and handshake time. Paper will also look at ways to increase security by integrating the CoAP I-DTLS protocol with the Secure Hash Algorithm (SHA-256) and utilizing Certificate Authority (CA) improvements. Evaluation parameters such as Packet loss ratio, Data transmission time, and Energy consumption average are considered and detailed simulation results have been presented.